2022
DOI: 10.3390/biomedicines10010178
|View full text |Cite
|
Sign up to set email alerts
|

Novel Insight into the Mechanisms of the Bidirectional Relationship between Diabetes and Periodontitis

Abstract: Periodontitis and diabetes are two major global health problems despite their prevalence being significantly underreported and underestimated. Both epidemiological and intervention studies show a bidirectional relationship between periodontitis and diabetes. The hypothesis of a potential causal link between the two diseases is corroborated by recent studies in experimental animals that identified mechanisms whereby periodontitis and diabetes can adversely affect each other. Herein, we will review clinical data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 254 publications
(322 reference statements)
0
41
0
1
Order By: Relevance
“…Furthermore, age (41) and the socioeconomic factor may also influence some periodontal parameters (42). In the same way, current smoking (33) and diabetes (34) (9,24,43). We also calculated the DMFT index, which was higher in pSS patients than in control participants, as also reported in a previous study that evaluated Danish pSS patients (24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, age (41) and the socioeconomic factor may also influence some periodontal parameters (42). In the same way, current smoking (33) and diabetes (34) (9,24,43). We also calculated the DMFT index, which was higher in pSS patients than in control participants, as also reported in a previous study that evaluated Danish pSS patients (24).…”
Section: Discussionmentioning
confidence: 99%
“…At both time points of the study (D0 and D90), the investigators recorded all treatments in current use through face-to-face interviews with patients. A questionnaire on comorbidities, hypertension, dyslipidemia, diabetes and smoking was also applied to pSS patients and controls, since the last two conditions can influence oral health (33,34).…”
Section: Clinical Evaluationsmentioning
confidence: 99%
“…P. gingivalis had its effect on intestinal microbiota and adipose tissue inflammation, and played a role in the regulation of downstream genes (such as mTOR, S6K-1) in the branched-chain amino acids (BCAAs)-induced insulin resistance signal pathway [ 40 ]. A recent study showed that periodontitis is exacerbated by diabetes in three ways: (i) IL-17 increases periodontal dysbiosis and bacterial pathogenicity, (ii) the host’s response to the bacterial challenge is improved, and (iii) periodontal damage is increased [ 41 ]. Diabetes inhibits new bone formation by increasing the death of bone-forming cells and reducing the proliferation and differentiation of periodontal ligament stem cells (PLSCs) in osteoblasts [ 41 ].…”
Section: Periodontitis Associated With Other Systemic Diseasesmentioning
confidence: 99%
“…A recent study showed that periodontitis is exacerbated by diabetes in three ways: (i) IL-17 increases periodontal dysbiosis and bacterial pathogenicity, (ii) the host’s response to the bacterial challenge is improved, and (iii) periodontal damage is increased [ 41 ]. Diabetes inhibits new bone formation by increasing the death of bone-forming cells and reducing the proliferation and differentiation of periodontal ligament stem cells (PLSCs) in osteoblasts [ 41 ].…”
Section: Periodontitis Associated With Other Systemic Diseasesmentioning
confidence: 99%
“…Da mesma forma, o tabagismo atual (Kassirer, 1994;Jiang et al, 2019;Watt et al, 2019;Kapila, 2021) e o diabetes (Coelho et al, 2020;Luong et al, 2021;Barutta et al, 2022) podem influenciar o estado de saúde dental e gengival.…”
Section: Discussionunclassified